HUBUNGAN ADVERSITY QUOTIENT DENGAN KESIAPAN BELAJAR PADA MATA PELAJARAN PAI - Dede Fatchuroji (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2020)
This study aims: (1) to describe the Adver- sity Quotient of the XII grade students of Madrasah Aliyah Negeri 1 Serang Regency; (2) to describe the learning readiness of class XII students of Madrasah Aliyah Negeri 1 Serang Regency; (3) to explain the relationship between Adver- sity Quotient and the students' learning readiness of class XII Madrasah Aliyah Negeri 1 Serang Regency. The method used by researchers is descriptive method with a quantitative approach. Population of 207 class XII students from 7 groups was then taken randomly from 32 students. Data collection technique. Data collection using a questionnaire instrument. This research was conducted from June to September 2019. Primary data sources were obtained from 15 questionnaires. Data processing used SPSS 16.0. Based on the results of data analysis, three conclusions were obtained as follows: First, Adversity Quotient class XII Madrasah Aliyah Negeri 1 Serang Regency is in the high category indicated by the mean value of 52.75. Second, the learning readiness of class XII Madrasah Aliyah Negeri 1 Serang Regency is in the medium category, indicated by a mean value of 59.06. Third, there is a significant positive relationship between Adversity Quotient and learning readiness. This is indicated by the value of Pearson correlation = 0.551 with sig 0.001, this value after being consulted with the interpretation table for the number